Scientific-Cum-Doctriner dalam Studi Islam Menurut Mukti Ali (Studi Analisis Perspektif Worldview Islam) - Asep Awaludin; Manzilatul Fadhilah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2022)
This article analyzes Mukti Ali's Scientific-Cum-Doktriner perspective which is called an approach that is the result of a combination of three different approaches. For Mukti Ali, this approach is the most suitable to be used in understanding Islam. However, this approach comes from Western thought. Thus, this study reveals several reasons for the presence of the Scientific-Cum-Doctriner approach. If it is highlighted from the causes and objectives of the emergence of this approach, it actually requires a solid foundation of faith so that it does not cause errors in the mindset of humans, especially Muslims. So, the concept of Islamic Worldview in this study is used as a perspective that is applied in understanding Islamic Studies.